Testing the Effects of Independent Judiciaries on the Likelihood of Democratic Backsliding - Douglas Gibler and Kirk Randazzo (My University, 2016)
We test the efficacy of judicial independence in preventing regime reversals toward authoritarianism. Using a dataset of judicial constraints across 163 different countries from 1960 to 2000, we find that established independent judiciaries prevent regime changes toward authoritarianism across all types of states. Established courts are also capable of thwarting regime collapses in nondemocracies. These results provide some of the first large-n evidence confirming the ability of the judiciary to maintain regime stability. Unfortunately, however, the beneficial effects of court systems seem to take time to develop. The evidence indicates that newly formed courts are positively associated with regime collapses in both democracies and nondemocracies.